Analisa Kekasaran Bearing 22224 Dan 29420 Mesin Screw Press Di PTPN XYZ - Mahyunis, Mahyunis; Effendi, Zulham; Renaldy, Muhammad Aziz (Rekayasa Material, Manufaktur dan Energi, 2024)
Palm Oil Mill (POM) is a plantation company that specializes in palm oil commodities with outputs in the form of CPO (Crude Palm Oil) and PK (Palm Kernel). At PTPN xyz there is a machine for extracting palm oil, namely a screw press, in the screw press there are bearing that supports the perfomance of the machine. This research aims to determine the surface roughness of the bearing, a comparison of the roughness value with the ISO (International Standard Organization) as well as the life time data of the bearing material which is adjusted to its specification. The research method used in this study is a qualitatif descriptive method using primary and secondary data. From the results of this research, the research of the analysis of the surface roughness values of bearing 22224 and 29420 were obtained, namely that the bearing experienced a decrease in roughness values from international standard organization standard using roughness tester, suffcorder SE300, Model AS-300, standard tool JIS2001R, series number MEX08756-36, Cut off 2,5mm, speed 0,2mm in µm (Micronmeter).